2019
DOI: 10.3233/jad-181295
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Treated Pneumonia Associated with Opioid Use Among Community Dwellers with Alzheimer’s Disease

Abstract: Background: Pneumonia is a common cause for hospitalization and excess mortality among persons with Alzheimer's disease (AD), but little research exists evaluating drug use as its risk factor.Objective: We investigated the association between opioid use and hospital-treated pneumonia among community dwellers with AD.Methods: This study was part of the Medication use and Alzheimer's disease (MEDALZ) cohort. We included all community dwellers newly diagnosed with AD during 2010-2011 in Finland with incident pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“… 22 Our study demonstrated an increased odds ratio for 30-day mortality among IBD patients treated for pneumonia (AOR 13.21, 95% CI 1.29–135.18, p = 0.03). Some of the physiologic effects of opiates are reduced cough reflex, slow and shallow respirations and impaired secretions clearance, 23 25 all of which may contribute to development of pneumonia. In addition, some opiate agents are known to impair the innate and adaptive immune systems, weakening the defense system against causative pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 Our study demonstrated an increased odds ratio for 30-day mortality among IBD patients treated for pneumonia (AOR 13.21, 95% CI 1.29–135.18, p = 0.03). Some of the physiologic effects of opiates are reduced cough reflex, slow and shallow respirations and impaired secretions clearance, 23 25 all of which may contribute to development of pneumonia. In addition, some opiate agents are known to impair the innate and adaptive immune systems, weakening the defense system against causative pathogens.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In addition, it was observed that opiates use among community dwellers with Alzheimer’s disease was associated with a 34% increased risk of hospital treated pneumonia compared with non-users. 24 A recently published large cohort study of 25,392 participants demonstrated a strong, independent association between prescribed opioids and the risk of CAP requiring hospitalization. 25 Furthermore, a dose-dependent effect of this association has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…86,89 Also, weak opioids were associated with a reduced risk of hospital-treated pneumonia among Alzheimer's disease patients compared with strong opioids (aHR of 1.54 (1.09-2.17) vs. 2.83 (1.89-4.24)). 90 Moreover, regardless of opioid strength or immunosuppressive features, highest risk was observed during the first two months of use (aHR 2.58, (1.87-3.55)), and disappeared after prolonged use (> 180 days) (0.91 (0.62-1.33)), as for OA patients under chronic management.…”
Section: Reviewmentioning
confidence: 95%
“…91 Depends on immunosuppressive (IS) and/or weak/strong activities. Absence of IS and/or weak activities are related with reduced pneumonia incidence 86,89,90 Strong Increased influenza-like illness 115 Anti-TNF-α mAb may reduce ACE2 expression. 122 Anti-IL-1β may be beneficial for coronavirus-related complications 126 No evidence for experimental use of mAbs in OA and COVID-19 patients except compassionate use ACE2, angiotensin-converting enzyme 2; AEs, adverse events; COVID-19, coronavirus disease 2019; CVD, cardiovascular disease; IL, interleukin; MERS, Middle East respiratory syndrome; mAbs, monoclonal antibodies; NSAIDs, nonsteroidal antiiflammatory drugs; OA, osteoarthritis; SARS, severe acute respiratory syndrome; TNF, tumor necrosis factor.…”
Section: Oa Drugs and Viral Infections: What Do We Know?mentioning
confidence: 99%